Semantic Smart World Framework. (20th January 2020) - ElDahshan, K.; Elsayed, E. K.; Mancy, H.
Abstract : This paper presents a general Semantic Smart World framework (SSWF), to cover the Migratory birds' paths. This framework combines semantic and big data technologies to support meaning for big data. In order to build the proposed smart world framework, technologies such as cloud computing, semantic technology, big data, data visualization, and the Internet of Things are hybrid. We demonstrate the proposed framework through a case study of automatic prediction of air quality index and different weather phenomena in the different locations in the world. We discover the association between air pollution and increasing weather conditions. The experimental results indicate that the framework performance is suitable for heterogeneous big data.